Geographic variation in racial disparities in child maltreatment: The influence of county poverty and population density. (September 2015) - Maguire-Jack, Kathryn; Lanier, Paul; Johnson-Motoyama, Michelle; Welch, Hannah; Dineen, Michael
Abstract: There are documented disparities in the rates at which black children come into contact with the child welfare system in the United States compared to white children. A great deal of research has proliferated aimed at understanding whether systematic biases or differential rates of risk among different groups drive these disparities (Drake et al., 2011 ). In the current study, county rates of maltreatment disparity are compared across the United States and examined in relation to rates of poverty disparity as well as population density. Specifically, using hierarchical linear modeling with a spatially lagged dependent variable, the current study examined data from the National Child Abuse and Neglect Data System (NCANDS) and found that poverty disparities were associated with rates of maltreatment disparities, and densely populated metropolitan counties tended to have the greatest levels of maltreatment disparity for both black and Hispanic children. A significant curvilinear relationship was also observed between these variables, such that in addition to the most densely populated counties, the most sparsely populated counties also tended to have higher rates of maltreatment disparity for black and Hispanic children.